The European Union's Africa policies norms, interests and impact - Sicurelli, Daniela (Ashgate Pub., 2010)
Mainstream studies have interpreted the EU's role in Africa as either a self-interested hegemonic actor or as a value oriented normative power. Sicurelli challenges these views by taking a closer look at Europe's policies towards sub-Saharan Africa in the area of trade, peacekeeping, and environmental protection.